Cidade de Belém e natureza: uma relação problemática? - LOUREIRO, Violeta Refkalefsky (Núcleo de Altos Estudos Amazônicos, 2011)
In an unstoppable and rapid manner, Belém is losing it’s urban green. This loss presents itself with unique characteristics when compared to other Brazilian cities, that equally suffer from the urban speculation and the chaotic occupancy of the land. The mango trees – witch are listed as part of the State’s patrimony as common goods and must be permanently preserved – are actually the most endangered species, no longer characterizing Belém as the mango tree’s city. Besides, differently from the other capitals, where the private sector has been the most res ponsible for the environment damage, in Belém, actions and omissions of the government to the city are more important to the deterioration of the urban landscape, it’s green areas and waters than the private sector.